RAISED LEVEL OF LIPOPROTEIDE(A) AS A PREDICTOR OF CARDIOVASCULAR COMPLICATION POST REVASCULARIZATION OF THE LOWER ExTREMETIES ARTERIES - N. A. Tmojan; О I. Afanasieva; A. Е. Zotikov; E. A. Klesareva; M. M. Abdulgamidov; М. V. Ezhov; A. V. Pokrovsky; S. N. Pokrovsky (Российский кардиологический журнал, 2018)
Aim. Lipoproteide (a) (Lpa) is a pathogenetic risk factor of cardiovascular atherosclerotic disease. On the role of Lpa in the development of cardiovascular complications (CVC) after lower limbs arteries revascularization, there is lack of data. The aim of the study was assessment of Lpa relation to CVC occurrence after revascularization of lower extremities during 1 year follow-up.Material and methods. In the study, 111 patients were included (97 males, 14 females, mean age 66±9 y.o.), who had undergone revascularization of lower libms arteries due to atherosclerosis. As CVC during 1 year follow-up, the following were taken: recurrent intermittent claudication, lower extremity amputation, ischemic stroke, transient cerebral ischemia, non-fatal myocardial infarction, unstable angina, repeat revascularization and cardiovascular death. In all patients, in the blood serum, there were measured lipids and Lpa.Results. Within 1 year after revascularization there were 45 (41%) CVC. In the group with raised Lpa ≥30 mg/dL there were more CVC than in Lpa <30 mg/dL: relative risk 2,1 (95% CI 1,3-3,5; p=0,004). Hence the increased level of Lpa is an independent predictor of CVC after revascularization of lower extremities arteries.Conclusion. In prospective study, during 1 year after revascularization the level of Lpa ≥30 mg/dL is associated with double increase of the risk of CVC.